PENGEMBANGAN MODUL AJAR KEARIFAN LOKAL KOMUNITAS SUKU ANAK DALAM UNTUK MENINGKATKAN KARAKTER CINTA BUDAYA SISWA SMPN 14 MUARO JAMBI - Darmawis; Ahmad Suryadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the unavailability of co-curricular teaching modules based on local wisdom of the Orang Dalam Tribe Community (SAD) at SMP Negeri 14 Muaro Jambi, so that local culture learning has not been carried out optimally and has an impact on the low understanding and love of students for regional culture. This study aims to describe the initial condition of students' love for culture, develop a Co-Curricular Teaching Module based on Local Wisdom of the Orang Dalam Tribal Community (SAD), and test the feasibility and effectiveness of the module in improving the learning outcomes and character of students' love for culture. The research uses the Research and Development (R&D) method with the ADDIE development model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of 30 students of SMP Negeri 14 Muaro Jambi. Data collection was carried out through observation, interviews, questionnaires, as well as pretest and posttest tests. Data analysis used descriptive statistics, validity test, reliability test, Shapiro-Wilk normality test, Paired Sample t-test, and N-Gain test. The results of the study showed that the modules developed obtained a validity rate of 96.67% from material experts and 95.00% from media experts with the very valid category, as well as a teacher's practicality level of 94.00% with the very practical category. The results of the implementation showed an increase in the average score of students from 54.63 in the pretest to 84.70 in the posttest. The Paired Sample t-test produced a significance value of 0.000 (p < 0.05), while the average N-Gain of 0.67 was in the medium category. Thus, the Co-Curricular Teaching Module based on Local Wisdom of the Orang Dalam Tribal Community (SAD) is declared valid, practical, and effective.